HPLC Analysis of an Ayurvedic Formulation - Kulkarni, V.S.; Surana, S.J. (Asian Journal of Chemistry, 2011)
In Ayurveda Intuppukana Churna is commonly prescribed as anti anorectic formulation which is the mixture of Terminalia chebula (Combretaceae), Piper longum (Piperaceae), Trachyspermum roxberghianum (Umbelliferae) and rock salt. Gallic and, ellagic acid and piperine are three markers present in the formulation, which were analyzed simultaneously by HPLC with PDA detector at 280 nm by using waters symmetry C-18 Column (250 × 4.6 mm, particle size 5 μ) at an ambient temperature. The separation was achieved with isocratic elution using a mixture of water: methanol (70:30) at pH 3.0 by addition of orthophosphoric acid at a flow rate of 0.8 mL/ min. Calibration curves were linear with correlation coefficients of 0.9941, 0.9968 and 0.9917 for gallic acid, ellagic acid and piperine, respectively over a concentration range of 10-100 μg/ mL for each. The validation parameter showed that the method is a simple, economical, specific, reproducible and accurate for the evaluation of these three markers in the Ayurvedic medicines.